Evaluation of Complications of Root Canal Treatment Performed by BDS Fresh Graduates (Medical Forum Monthly, 2024)
Objective: This current case actually aimed at radiographic assessment of quality of RCT along with procedural and technical errors evaluation by free BDS fresh graduates during era of 2015 to 2018 at Dental OPD of different hospitals.Study Design: Observational study.Place and Duration of Study: This study was conducted at the Department of Oral Medicine, Avicenna Dental College Lahore from March 2017 to March 2019.Materials and Methods: A chart was recorded to register record of RCT quality and its outcomes in 280 patients handled by fresh graduates. This case was performed at dental OPD of different hospitals, in which the root canal treatment outcome quality and shortcomings by BDS fresh graduates was judged.Results: The results were recorded based on root canal obturation, its good adoption to root canal walls and obturated apex radiodenstisty ≤2 mm as compared to apex from radiograph of respected tooth. The root obturation that was not up to standard measurements were ended in root canal failures such as ledge formation, canal transportation, furcal perforation, instrument separation, strip formation, formation of voids and over and under filling of obturated material. It was estimated in case study that 87 patients (31.1%) had inadequate RCT whereas 193 (68.9%) patients were treated successfully by fresh graduates without any procedural defects.Conclusion: It was finally concluded that RCT performed by an undergraduate student in 68 percent cases was adequate and without any technical and procedural errors, where as in 31.1 precent RCT was inadequate. The technical and procedural errors were mostly in molars and procedure that was not done adequately was obturation of root canal (under filling). The fresh graduates and final year students had same technical and procedural errors with no prominent differences.